2015
DOI: 10.7243/2055-7205-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual activity in older Malaysian adolescents and associated factors

Abstract: Background: Unprotected sexual activity predisposes adolescents to serious consequences later in life. This study aimed to identify the risks and protective factors associated with sexual activity in Malaysian adolescents aged 18 to 19 years. Methods: Data from a health screening program among adolescents conducted in 2010 were analyzed. A total of 21,438 unmarried adolescents responded to this topic using a self-administered non-anonymous validated questionnaire. Results: Among the participants, 54.5% were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
4
25
4
Order By: Relevance
“…Another recent study conducted by Lodz et al (2019) on the risk of sexual behaviours among school-going adolescents in Malaysia reported the prevalence of ever had sex among the adolescents in Malaysia was 7.3%, with most of them were males and Indian. Chinese also has been reported to have a higher risk to be involved in the sexual activity compared to the Malay according to the Malaysian National Health Program (Awaluddin et al, 2015). In line with a study by Abdullah et al (2020), this study results showed significant association between ethnicity and intention towards sexual activity.…”
Section: Variablessupporting
confidence: 87%
See 1 more Smart Citation
“…Another recent study conducted by Lodz et al (2019) on the risk of sexual behaviours among school-going adolescents in Malaysia reported the prevalence of ever had sex among the adolescents in Malaysia was 7.3%, with most of them were males and Indian. Chinese also has been reported to have a higher risk to be involved in the sexual activity compared to the Malay according to the Malaysian National Health Program (Awaluddin et al, 2015). In line with a study by Abdullah et al (2020), this study results showed significant association between ethnicity and intention towards sexual activity.…”
Section: Variablessupporting
confidence: 87%
“…In Malaysian culture, in which the majority of the populations are Malay, sex remains a taboo and is a sensitive issue to be discussed (Ismail & Abd Hamid, 2016). Although the reported number of adolescents engaged in premarital sex in Malaysia is low compared to other western countries (Awaluddin et al, 2015), the number does not match with the rising number of teenage pregnancies every year. The reason for this is Malaysian adolescents are not free to disclose about sex, or to share about their sexual life experiences (Wong, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Contraceptive will prevent STDs and arrest unintended pregnancies [29]. Unprotected sexual activity predisposes the adolescents to serious consequences later in life [30]. Apart from that, about 88.3% in this study showed their attitude of opposing premarital sex, but their practice was contrary because 100% of the participants in this study were single and had sexual experience before this.…”
Section: Discussionmentioning
confidence: 87%
“…Similar results have also been found in other studies. 3,6,[9][10][11][12] These activities provided more opportunities to socialise with the opposite gender as well as those with high-risk behaviours. As a result, they were more likely to experiment with high-risk behaviours practised by their peers and adopt a liberal attitude towards dating, physical intimacy and premarital sexual activities.…”
Section: Discussionmentioning
confidence: 99%